2011
DOI: 10.1159/000330546
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherotomy or Lobectomy? The Role of Presurgical Neuroimaging in a Young Case of a Large Porencephalic Cyst with Intractable Epilepsy

Abstract: A young patient with a large left hemisphere porencephalic cyst underwent neuroimaging investigation (functional magnetic resonance imaging (fMRI), EEG-fMRI, DTI tractography) during presurgical evaluation for intractable epilepsy. The functional workup showed that (a) the healthy hemisphere had undertaken language processing, primary and secondary sensory functions of bilateral upper and lower extremities, and bilateral feet motion, and (b) the porencephalic hemisphere had retained contralateral arm and shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Of the analyzed studies, seven reported the use of DTI and its relationship to the patient’s motor outcome. 20,41,45,48–51 The studies by Kokkinos and Shinoda were case reports in which DTI was used to assess the relationship of the corticospinal tracts (CST) with the region of interest resulting in a tailored surgical plan to avoid this tract resulting in preservation of motor function in both patients.. 41,45 Yang et al reported on a prospective study analyzing 16 patients and using HARDI diffusion-weighted data which enabled a tailored surgical plan resulting in 100% preservation of post-operative motor function. 20 Finally, the last three studies by Nelles, Jeong and Wang focused on the use of DTI for predicting motor outcome after epilepsy surgery and showed that quantitative values calculated with DTI, such as FA and the robustness of the CST, can accurately predict post-operative motor function with a specificity that ranges between 69.6 and 100% and a sensitivity of 80–85.7% 49–51 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the analyzed studies, seven reported the use of DTI and its relationship to the patient’s motor outcome. 20,41,45,48–51 The studies by Kokkinos and Shinoda were case reports in which DTI was used to assess the relationship of the corticospinal tracts (CST) with the region of interest resulting in a tailored surgical plan to avoid this tract resulting in preservation of motor function in both patients.. 41,45 Yang et al reported on a prospective study analyzing 16 patients and using HARDI diffusion-weighted data which enabled a tailored surgical plan resulting in 100% preservation of post-operative motor function. 20 Finally, the last three studies by Nelles, Jeong and Wang focused on the use of DTI for predicting motor outcome after epilepsy surgery and showed that quantitative values calculated with DTI, such as FA and the robustness of the CST, can accurately predict post-operative motor function with a specificity that ranges between 69.6 and 100% and a sensitivity of 80–85.7% 49–51 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The other 20 % of the operations were extra-temporal epilepsy cases with focal cortical resections and occasionally multilobar resections. Acute intraoperative ECoG is utilized in most temporal and extra-temporal cases for confirmation of epileptogenicity and modifications of resections in selected cases [26, 59, 60]. Follow-up information is available on a yearly basis for at least 90 % of the operated patients with 80 % of the patients having an Engel class I outcome, 15 % a class II–III, and 5 % a class IV outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Microcephaly is generally related. 5,6 The differential diagnosis of porencephaly includes schizencephaly, arachnoid cyst, cystic neoplasm and hydrocephalus. In schizencephaly there are fissures with smooth outline while in porencephaly, the cysts are round with jagged contours and there may be thrombus or detritus.…”
Section: Discussionmentioning
confidence: 99%